2019
DOI: 10.1111/1460-6984.12474
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the speech and language of individuals with non‐syndromic submucous cleft palate: a preliminary report

Abstract: Background: Submucous cleft palate (SMCP) has a heterogeneous presentation and is often identified late or misdiagnosed. Diagnosis is prompted by speech, resonance or feeding symptoms associated with velopharyngeal insufficiency. However, the broader impacts of SMCP on communication have rarely been examined and therefore are poorly understood. Aim: To describe the communicative profile of individuals with non-syndromic SMCP by examining speech, language and pragmatics (social language). Methods & Procedures: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
2
0
1
Order By: Relevance
“…The questionnaire targeted the domains speech, language, communication and pragmatic/social interaction skills. Speech was rated to cause the greatest difficulties with communication in everyday live, which is in line with a previous study on children with SMCP aged 5 to 12:8 (Boyce et al, 2019). In addition, interesting results were found in the parental rating of Syntax, which was below -2 SD scores for all participants with CAS+DLD (n=7).…”
Section: Functional Communication Associated With Severely Disorderedsupporting
confidence: 89%
“…The questionnaire targeted the domains speech, language, communication and pragmatic/social interaction skills. Speech was rated to cause the greatest difficulties with communication in everyday live, which is in line with a previous study on children with SMCP aged 5 to 12:8 (Boyce et al, 2019). In addition, interesting results were found in the parental rating of Syntax, which was below -2 SD scores for all participants with CAS+DLD (n=7).…”
Section: Functional Communication Associated With Severely Disorderedsupporting
confidence: 89%
“…18,61 Too early surgical intervention solely based on physical and magnetic resonance imaging examination may not be necessary, as speech development is variable even in the presence of obvious levator muscle dehiscence. 14,62 Although most previous studies reported an average age at operation younger than 9.5 years, none of them provided sufficient data to define the late range of SMCP operation timing. 22,30,44 Our data were not against the principle of delivering SMCP surgical intervention as early as hypernasality or nasal emission is diagnosed by reliable speech analyses.…”
Section: Discussionmentioning
confidence: 99%
“…18,61 Too early surgical intervention solely based on physical and magnetic resonance imaging examination may not be necessary, as speech development is variable even in the presence of obvious levator muscle dehiscence. 14,62 Although most previous studies reported an average age at operation younger than 9.5 years, none of them provided Copyright © 2023 American Society of Plastic Surgeons. Unauthorized reproduction of this article is prohibited.…”
Section: Discussionmentioning
confidence: 99%
“…Sie können allerdings auch unvollständig oder als vollständige Spaltung der oralen Schleimhaut, der Muskulatur und der nasalen Schleimhaut auftreten (Bernheim et al 2006). Als Sonderform der unvollständigen Weichgaumenspalten ist hier die submuköse Gaumenspalte zu erwähnen, bei der nur die Muskulatur des weichen Gaumens gespalten und fehlorientiert ist, weswegen die Spaltbildung häufig erst im Laufe der Sprachentwicklung entdeckt wird (Boyce et al 2019;Calnan 1954).…”
Section: Gaumenspaltenunclassified